Determinants of Farmer’s Attitude toward Organic Agriculture and Barriers for Converting to Organic Farming Systems: Research Insights - Janjhua, Yasmin; Chaudhary, Rashmi; Mehta, Piyush; Kumar, Krishan (International Journal of Economic Plants, 2019)
Organic farming is gaining acceptance all over the world due to associated benefits of quality food, enhanced soil health, environment protection, conservation of natural resources and taking care of human health. However, concern is whether farmers will change their farming systems which they have been practicing from long and shift to organic farming. The attitude and perceptions of farmers on organic farming systems have an impact on their behavioral tendencies. Consequently, the attitude is being shaped by various factors which stand as driving and restraining forces for the desired change. In the present paper, the review of various research studies provide insight into the factors that are considered important by the farmers for adoption of organic farming, the willingness and ability of farmers to change their current farming system and the problems that are perceived by the farmers in converting to organic farming system.